Peran Minat Baca dan Praktek Kewirausahaan Untuk Meningkatkan Hasil Belajar Kewirausahaan Pada Siswa SMK di Kabupaten Bogor Jawa-Barat - Sigit Widiyarto; Irfan Hadi; Siti Alifah; Nia Liska Saputri; Ronald Haries Hamonangan; Nia Damayanti; Lusiana Wulansari; Zeinora Zeinora (Peneliti.net, 2023)
Interest in reading among students is still low. Students are only able to understand the procedural text well. Procedure text is a text description that contains the text of a program and tool. Students are expected to have an interest in reading well. Entrepreneurial practice is an important factor in the success of entrepreneurship lessons. This research uses quantitative. There is an influence of reading interest on entrepreneurship learning outcomes, there is an influence of practice on entrepreneurship student learning outcomes and there is a guide for reading interest and entrepreneurship practice on entrepreneurship learning outcomes for students of SMK Mulia Kencana, Bogor district. Respondents were 43 students of class XI SMK Mulia Kencana. Data is processed using SPSS 22. Data is processed by reliability and collinearity tests, then processed by hypothesis testing and the r Square test. Entrepreneurship learning needs to be improved in quality and attention for teachers and the government. Schools can reactivate programs to increase interest in reading and entrepreneurial practice